Defining the possible therapeutic benefit of lymphadenectomy among patients undergoing hepatic resection for intrahepatic cholangiocarcinoma. Issue 6 (3rd March 2016) - Vitale, Alessandro; Moustafa, Mohamed; Spolverato, Gaya; Gani, Faiz; Cillo, Umberto; Pawlik, Timothy M.
Abstract : Background: The aim of the study was to investigate the therapeutic role of lymphadenectomy (LND) in patients with intrahepatic cholangiocarcinoma. Methods: 826 patients who underwent liver resection were identified using the SEER database from 1988 to 2011. Two groups of patients were defined: 201 (24%) undergoing potentially therapeutic LND (group A, >3 lymph nodes (LN) removed), and 625 (76%) not receiving therapeutic LND (group B, ≤3 LNs removed). A propensity score analysis was performed to create a matched cohort of 402 patients (201 in either group). The survival benefit of therapeutic LND was also estimated using multivariate parametric analysis comparing two simulated cohorts of 826 patients. Results: 1‐, 3‐, and 5‐year survival rates were 71%, 37%, and 27% for group A patients, and 73%, 37%, and 27% for matched group B patients ( P = 0.656). When simulation analysis was performed, a moderate survival benefit of LND of 5.46 months was calculated (95%CI, 4.64–6.29). Considerable differences in LND survival benefit predictions were found according to patient's sex (males, 9.90 vs. females 1.16 months), age (≤60 years, 15 vs. >60 years, −1.34 months), and tumor size (>50 mm, 9.20 vs. ≤50 mm, −0.28). Conclusions: LND therapeutic benefit among a subset of patients. Future work is required to investigate the role of routine LND among these patients. J. Surg. Oncol. 2016;113:685–691 . © 2016 Wiley Periodicals, Inc.